THE EFFECT OF HYDROGEL DRESSING COPOLYMER POLI(VINYLPIRROLIDONE) (PVP) - k- CARRAGEENAN PREPARED BY RADIATION AND HEALING TIMES ON THE RADIUS REDUCTIONS BURN INJURIED OF WISTAR WHITE RAT - Erizal Erizal (Universitas Gadjah Mada, 2008)
The pre-clinical study of poly (vinyl pirrolidone) (PVP)-k- carrageenan hydrogel has been carried out. The aim of this study is to investigate the effect of hydrogel for healing burn injuried in the rats. The hydrogels were prepared by g-irradiation of aqueous solutions of 15 wt.-% PVP and 2 wt.-% k- carrageenan at a sterilization dose of 25 kGy. The physico-chemical properties of hydrogels were investigated. The results showed that the hydrogels suitable as candidate for wound dressing with gel fraction of 90 ± 5 (%), the water absorption was 4500 ± 55 (w/w), the water content was 83 ± 2 (%), tensile strength was 1,5 ± 0,1 kg/cm2 and adhesiveness was 0. The effect of the hydrogel as wound dressing was evaluated by attaching to a burn of the back skin of rats as a function of time observation. Advantages of the hydrogel were slightly faster rate of reducing radius diameter of injured burn skin, easy removal without damage to renewed skin.